Overview of the study of psychological preparation in Chess (Review) (Revista científica Olimpia, 2021)
Psychological preparation is one of the fundamental components for the training of the athlete, as it guarantees mastery of himself and safety in the execution of different skills. It is a pedagogical process; whose purpose is to prepare the athlete to perform his best performance at the time of the competition. Disciplines that require high-order cognitive skills and have positive effects on their development include chess. The study of these mental skills poses great demands from a psychic point of view to its practitioners and that is why, from the beginning of the preparation of the chess player, he must receive a psychological accompaniment that allows him to overcome all the difficulties he faces from training to after the competition. The objective of this work is to establish the main theoretical budgets on the psychological preparation of chess players, based on their inherent characteristics.
Keywords: preparation psychological; chess; sports performance; mental abilities